1H NMR spectrometry for methanol quantification in apple wines and ciders as optimised by comparison to SIDA-HS-GC-MS. (1st September 2022) - Convertini, Raphael; Patz, Claus; Kumar, Keshav; May, Bianca; Andlauer, Wilfried; Schweiggert, Ralf
Highlights: 1 H NMR was optimised against SIDA-HS-GC–MS for methanol quantification in alcoholic beverages. A correction factor (Kexternal = 1.2347) improved methanol quantification accuracy by 1 H NMR. 1 H NMR method was successfully validated using reference data from three interlaboratory trials. Method optimization included a reduction of the quantification limit. Methanol in 133 commercial products was quantitated and discussed. Abstract: Methanol, a hepato- and neurotoxic compound, is present in apple-based beverages as a by-product of the enzymatic degradation of pectin. Stable isotope dilution assay (SIDA) employing gas chromatography-mass spectrometry (GC–MS) is the state-of-the-art method for methanol determination in beverages. Despite higher initial investment costs, quantitative 1 H NMR spectroscopy (qNMR) is a simpler and faster analytical technique to quantify numerous analytes in liquid foods. Beyond targeted analyses, qNMR spectral fingerprints in the product might be used for non-targeted analytical goals, such as adulteration and contamination detections. Here, an existing 1 H-qNMR method used for wine profiling was optimised for methanol quantification in apple-based products, including cross-validation against a SIDA-HS-GC–MS method and reference values from interlaboratory trials. The optimisation involved a pivotally important estimation of a correction factor by an external calibration approach, making qNMR results comparable to SIDA-HS-GC–MS. The optimised qNMR method is suggested to be an alternative for methanol quantification in beverages.